Monocular Electrical Cataract: A Case Report: Poster Presentation - Case Report - Ophthalmologist - Ey, Merry Giovedi; Dewanto, Erry; Prastayani, Reni (Majalah Oftalmologi Indonesia, 2023)
Introduction : An electric shock is experienced when an electric current passes through a part of the body from an entry point to an exit point. Cataract is frequently described as a complication of electrical injury and it is usually bilateral. We report a rare case of high voltage electric injury in young male patient resulting in monocular cataract. Case Illustration : A 23 years old man was presented with a diminution of vision one year after sustaining an overhead high voltage power transmission wire that stung his head. The visual acuity of the right eye was hand movement dan 1.0 in the left eye. On slit-lamp examination, opacities were presented in the lens of the right eye and a clear lens in the left eye. Being diagnosed as having monocular cataract, the patient was then performed phacoemulsification on his right eye (April 12th 2023). The pupil shrank until 5 mm during the surgery but foldable IOL was successfully inserted in the capsule. The right eye vision was improved to 0.5 one day after surgery. Discussion : The consequences of high-voltage electric burns are complex. Electrical shock can cause protein coagulation and cataract formation. Lens manifestations are more likely when the transmission of current involves the patient’s head. Proper management of electrical cataracts will result in good visual rehabilitation if the eye does not suffer additional damage as in this case. Conclusion : Secondary cataract formation due to electric injury may occur, therefore routine examinations with the ophthalmologist are needed after the electrical trauma. The incidence of monocular cataracts after the electric injury is rare.